2010
DOI: 10.1890/09-0859.1
|View full text |Cite
|
Sign up to set email alerts
|

Foliar fungal pathogens and grassland biodiversity

Abstract: By attacking plants, herbivorous mammals, insects, and belowground pathogens are known to play an important role in maintaining biodiversity in grasslands. Foliar fungal pathogens are ubiquitous in grassland ecosystems, but little is known about their role as drivers of community composition and diversity. Here we excluded foliar fungal pathogens from perennial grassland by using fungicide to determine the effect of natural levels of disease on an otherwise undisturbed plant community. Importantly, we excluded… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
91
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(99 citation statements)
references
References 78 publications
8
91
0
Order By: Relevance
“…Patterns of plant demography consistent with Janzen-Connell effects are found in tropical forests (Metz et al 2010), temperate forests (Martin and Canham 2010), and grasslands (Petermann et al 2008, Allan et al 2010, and throughout the early life stages of trees, from seeds (Kotanen 2007) to seedlings to saplings (Gonzalez et al 2010). Patterns of plant demography consistent with Janzen-Connell effects are found in tropical forests (Metz et al 2010), temperate forests (Martin and Canham 2010), and grasslands (Petermann et al 2008, Allan et al 2010, and throughout the early life stages of trees, from seeds (Kotanen 2007) to seedlings to saplings (Gonzalez et al 2010).…”
Section: Discussionsupporting
confidence: 53%
“…Patterns of plant demography consistent with Janzen-Connell effects are found in tropical forests (Metz et al 2010), temperate forests (Martin and Canham 2010), and grasslands (Petermann et al 2008, Allan et al 2010, and throughout the early life stages of trees, from seeds (Kotanen 2007) to seedlings to saplings (Gonzalez et al 2010). Patterns of plant demography consistent with Janzen-Connell effects are found in tropical forests (Metz et al 2010), temperate forests (Martin and Canham 2010), and grasslands (Petermann et al 2008, Allan et al 2010, and throughout the early life stages of trees, from seeds (Kotanen 2007) to seedlings to saplings (Gonzalez et al 2010).…”
Section: Discussionsupporting
confidence: 53%
“…In natural grasslands, fungal pathogens are predicted to maintain plant species co‐existence by lowering the abundance of dominant plant species (Petermann et al ., ; Allan et al ., ). A previous study in our plots revealed that A .…”
Section: Discussionmentioning
confidence: 97%
“…We observed a decline in population size and recruitment rates over the study period. Other studies have shown that disease may reduce both seed quality in subsequent generations (Jarosz, Burdon & Muller ) and competitive ability in relation to other species (Paul & Ayres ; Paul ; Friess & Maillet ; Allan, van Ruijven & Crawley ). Although we do not have direct evidence of the effects of M. lini infection on seed quality or plant competitive ability, there is clearly potential for such disease effects to profoundly alter plant community structure (Borer et al .…”
Section: Discussionmentioning
confidence: 99%
“…Although we do not have direct evidence of the effects of M. lini infection on seed quality or plant competitive ability, there is clearly potential for such disease effects to profoundly alter plant community structure (Borer et al . ; Allan, van Ruijven & Crawley ). Notwithstanding these effects, it is most likely that the decline in the Kiandra L. marginale population was also strongly influenced by vegetational successional processes – increasing density of grass and herb cover and encroachment by a range of low shrubs (Leigh et al .…”
Section: Discussionmentioning
confidence: 99%